Numerical and experimental study of a FORM-based design wave applying the HOS-NWT nonlinear wave solver. (1st November 2022) - Kim, Shinwoong; Bouscasse, Benjamin; Ducrozet, Guillaume; Canard, Maxime; De Hauteclocque, Guillaume; Ouled Housseine, Charaf; Ferrant, Pierre
Abstract: This paper presents a comparative study of long-time irregular waves and equivalent design waves (EDW) in terms of geometric similarity and probability of exceedance (POE) distribution of the wave crest. For a proper comparison between the two wave types, the same nonlinear model was applied in the wave generation by application of the Higher-Order Spectral-Numerical Wave Tank (HOS-NWT), a fully nonlinear propagation solver. Numerical and experimental Monte-Carlo results were obtained through a number of realizations of a given sea state, and results were used as a reference for the EDW results. The experimental measurements and numerical simulations for a given sea state were analyzed and compared in terms of the wave spectrum estimation and the POE distribution of wave crests. The agreement between experimental and numerical results in wave quality seemed sufficient for it to be used as a reference for EDW cases. The First-Order Reliability Method (FORM) approach was applied in the calculation of EDW. The geometrical similarity between the measured EDW wave signal and the corresponding irregular wave signals measured in a given sea state was reviewed. It confirmed that the FORM-based EDW generates a comparable wave profile. In the statistical analysis, however, the results showed that for some EDW cases in relatively severe sea states, the POE estimates by the FORM method appeared to have conservative values compared to the Monte-Carlo reference POE distribution, whereas for the EDW cases in moderate sea states, the estimated POEs were in very good agreement with the empirical wave crest POE distribution of a given sea state. Highlights: Validation of HOW-NWT ability to reproduce crest statistics in breaking sea state through the cross-validation with experimental results. Development and validation of the FORM optimization algorithm coupled with the fully nonlinear wave solver HOS-NWT. Evaluation of geometrical characteristics and estimated crest statistics of the FORM-based EDW to the long-time irregular wave results.